Genetic analysis of uterine adenosarcomas and phyllodes tumors of the breast. Issue 8 (16th May 2017) - Geyer, Felipe C.; Burke, Kathleen A.; Piscuoglio, Salvatore; Ng, Charlotte K. Y.; Papanastasiou, Anastasios D.; Marchiò, Caterina; Selenica, Pier; Edelweiss, Marcia; Murray, Melissa P.; Brogi, Edi; Soslow, Robert A.; Rubin, Brian P.; et al.
Abstract : Uterine adenosarcomas and breast phyllodes tumors (PTs) are morphologically similar, being composed of stromal projections in a leaf‐like fashion lined by epithelial cells. Here, we investigated whether their histologic similarities would be mirrored at the genetic level. The previously reported repertoires of somatic genetic alterations found in 19 adenosarcomas and 22 PTs (six benign, six borderline, and 10 malignant) were compared. PTs significantly more frequently displayed mutations affecting MED12, the TERT gene promoter and bona fide cancer genes, whereas adenosarcomas harbored a higher rate of MDM2 / CDK4 and TERT gene amplifications. Pathway analyses based on the genes affected by somatic genetic alterations in these tumors indicated that Wnt signaling likely plays a role in the biology of adenosarcomas and benign/borderline PTs. In conclusion, despite the differences at the gene level, PTs and adenosarcomas share remarkable morphologic similarities and enrichment for somatic genetic alterations affecting Wnt pathway‐related genes. Abstract : We reanalyzed our previously published massively parallel sequencing data from 19 uterine adenosarcomas and 22 breast phyllodes tumors (six benign, six borderline, and 10 malignant) and made a systematic comparison of the results. Adenosarcomas and phyllodes tumors display quantitative and qualitative differences in regard to the repertoire of somatic genetic alterations they harbor. However, both tumor types appear to have enrichment for distinct somatic genetic alterations affecting genes related to the Wnt signaling pathway and to p53/pRb/cell cycle‐related pathways.